Improving the Pharmacists' Response to Public Health Emergencies-Documentary Research on Online Resources Provided by National Pharmacists' Associations - Alexandra Toma; Ofelia Crişan (Frontiers Media S.A., 2022)
Objectives: Given the expanding role of pharmacists during COVID-19 pandemic, we aimed to investigate the approach of professional associations to supporting their practice and to find ways to improve their response to public health emergencies.Methods: We conducted documentary research on websites of seven national pharmacists' associations, submitted the findings to a comparative thematic analysis, and made proposals of specific good practices.Results: Many great resources were provided by pharmacists' associations in Australia, France, Spain, and the US. The similarities include scientific information on COVID-19 tests, treatments and vaccines, legal issues, and wellbeing management. The main differences were in developing medication management programs, supporting hospital pharmacists, helping families, or advocating for an equitable vaccination. In Finland, Hungary and Romania, the focus was on updating emerging information. Considering the need for better managing public health emergencies at organizational level, we suggested good practices regarding training and communication.Conclusion: Professional associations should develop preparedness and response plans for public health emergencies. Practical training and effective communication could improve the resilience of pharmacists and patients during pandemics, which could save lives.